Ethnostatus Distinctions in the Western Canadian Subarctic: Implications for Inter-Ethnic and Interpersonal Relations - Waldram, James B. (Culture, 1987)
Subarctic ethnologists have rarely considered the implications of legal Indian and treaty status in their examinations of inter-ethnic and interpersonal relations. Utilizing the concept of ethnostatus, the author argues that Native identity must be seen as the product of the interplay between both cultural and legal/treaty status factors. Ethnostatus identities present themselves differently in different social, economic and political contexts. Inter-ethnic and interpersonal relations, therefore, are only partially governed by cultural factors, and in certain contexts the legal status of the role players seems to be paramount. Examples from the ethnographic literature are presented to support this argument.